The Origin of Arabic Lexicography: Its Emergence and Evolution - Niken Nur Hanifah (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2021)
This study aims to identify and describe 1) the history of the emergence and evolution of Arabic lexicography, 2) the implications of Arabic lexicography for learning Arabic. This research is a historical study using a qualitative approach with library research methods and documentation techniques. The data analysis used in this research is descriptive qualitative analysis. The results of the analysis show that 1) the emergence of al fikr al mu'jamiy was based on the difficulty of Arabs in understanding the meanings contained in the Qur'an which was named as gha>ri>bu al Quran, during this evolution period of Arabic lexicography gave an impact against the emergence of variations of the Arabic lexicon and entry systems with its characteristics one each other. This variety is the pure thought and innovation by lexicologists at that time in order to find the most appropriate method and system to codify Arabic vocabulary to make the Arabic lexicon provide an umbrella that can protect the purity and sustainability of the Arabic language from the challenges, 2) Arabic lexicography has a big impact in learning Arabic in the fields of morphology, syntax, and semantics which are language subsystems.